2007
DOI: 10.2193/2005-754
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Use of Sympatric Rattlesnake Species Within the Gulf Coastal Plain

Abstract: : The eastern diamondback rattlesnake (Crotalus adamanteus) and timber rattlesnake (Crotalus horridus) are sympatric throughout most of southern Georgia, USA. We used rattlesnake sightings to quantify and compare habitat use by these 2 species in the Gulf Coastal Plain. At the largest scale examined, univariate statistics and logistic regression models indicated that eastern diamondback rattlesnakes were associated with roads but not with any of the specific habitat types we examined. In contrast, timber rattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Some of this variation is most likely explained by differences among species in their behavioral responses to roads and traffic (Jaeger et al 2005, Fahrig andRytwinski 2009). Some turtles use roads and roadsides as nesting sites (Haxton 2000, Aresco 2005, Steen et al 2007) and some snakes have been reported to come to the road surface to bask during the day or to thermoregulate at night (Sullivan 1981, Rosen andLowe 1994). This combination of factors is most likely responsible for the frequent negative effects of roads and traffic on abundances of amphibians and reptiles (Fahrig and Rytwinski 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some of this variation is most likely explained by differences among species in their behavioral responses to roads and traffic (Jaeger et al 2005, Fahrig andRytwinski 2009). Some turtles use roads and roadsides as nesting sites (Haxton 2000, Aresco 2005, Steen et al 2007) and some snakes have been reported to come to the road surface to bask during the day or to thermoregulate at night (Sullivan 1981, Rosen andLowe 1994). This combination of factors is most likely responsible for the frequent negative effects of roads and traffic on abundances of amphibians and reptiles (Fahrig and Rytwinski 2009).…”
Section: Discussionmentioning
confidence: 99%
“…positive Steen et al (2007) timber rattlesnake (Crotalus horridus) negative Steen et al (2007) black ratsnake (Elaphe obsoleta) negative Row et al (2007) GalĂĄpagos lava lizard (Microlophus albemarlensis) (2005) Skylark (Alauda arvensis) negative Reijnen et al (1996) Meadow Pipit (Anthus pratensis) negative Reijnen et al (1996) Florida Scrub Jay (Aphelocoma coerulescens) Reijnen et al (1996) Mallard (Anas platyrhynchos) neutral/negative Reijnen et al (1996) Tufted Duck (Aythya fuligula) neutral/negative Reijnen et al (1996) Turkey Vulture (Cathartes aura) positive Coleman and Fraser (1989) Black Vulture (Coragyps atratus) positive Coleman and Fraser (1989) Mute Swan (Cygnus olor) neutral/negative Reijnen et al (1996) Coot (Fulica atra) negative Reijnen et al (1996) Sandhill Crane (Grus canadensis) attributes interact with the animal's behavioral responses to roads to affect animal abundances. If animals with very large movement ranges do not avoid roads, their high frequency of road crossing leads to a high overall probability of being killed at some point.…”
Section: Reasons For Negative Road Effectsmentioning
confidence: 99%
“…We used a combination of expert opinion (see below) and literature review to estimate home-range size and maximum dispersal distances. Though these two specialists are patchily distributed across similar habitats, they may tolerate different levels of fragmentation and roads (Steen et al, 2007;Hoss et al, 2010) while exhibiting a nearly twofold difference in maximum dispersal distance. Although these species have generalized habitat requirements, the black bear and timber rattlesnake are often highly associated with deciduous and bottomland hardwood forests (Larkin et al, 2004;Hoss et al, 2010), while the red wolf and eastern cougar are highly associated with agricultural pasture and forest edge habitats (Dellinger et al, 2013;Frakes et al, 2015).…”
Section: Target Speciesmentioning
confidence: 99%